Science in the Culture of the 20th Century - Minkevičius, Jokūbas (Problemos, 1984)
Having become an important part of the culture of the 20th century science marked it by essential features of technical civilization and made problematic the status of spiritual values. An anthropogenetic factor by its power of scientific-technical potency has become decisive for humanity. The problem of the harmony between culture and nature has arisen as well as that of criteria of the scientific-technical and socio-cultural progress. Fundamental problems of science as a phenomenon of culture must be discus in the context of the macro-system nature–society–culture. In this context science can perform its positive cultural function by means of self-fundamentalization, ecologization and humanization in harmony with other components of spiritual culture: philosophy, art, morality.